Elicitation of electricity consumption habit formation among new subscribers - Richard K. Moussa; Désiré K. Kanga (Heliyon, 2024)
In this study, our aim is to explore the formation of electricity consumption habits in Cote d'Ivoire, specifically focusing on new subscribers. The growth of residential electricity consumption globally has been influenced by these habits, which can lead to inertia and inefficient energy usage. Using the unique database of the National Electricity Company, we uncover that electricity consumption habits exhibit a high level of persistence, and this persistence tends to strengthen over time. These findings highlight the need to develop policies that encourage electricity efficiency among new subscribers, to combat energy inefficiency and foster positive consumption habits at the household level.